OVERVIEW OF SAFETY INCIDENTS INVOLVING PEDIATRIC PATIENTS AT A UNIVERSITY HOSPITAL - Dornfeld, Dinara; Hoffmann, Letícia Maria; Silveira, Marina Scherer; Pinheiro, Sabrina dos Santos; Paranaguá, Thatianny Tanferri de Brito; Breigeiron, Márcia Koja; Wegner, Wiliam (Cogitare Enfermagem, 2024)
Objective: To analyze the profile and characteristics of safety incidents that occurred between 2015 and 2019 with pediatric patients reported in the computerized system of a university hospital. Method: quantitative, descriptive, cross-sectional study with 2,558 notifications at an institution in southern Brazil. Descriptive statistics and the chi-square test were used to analyze the data. Results: higher occurrence of safety incidents related to medications/intravenous fluids (n = 643; 25.1%), diet/food (n = 448; 17.5%), clinical process/procedure (n = 384; 15.0%), medical devices/equipment (n = 304; 11.9%), and patient accidents (n = 273; 10.7%). Inpatient and intensive care units are more related to the occurrence of incidents; work shifts were not related to the type of incident reported. Conclusion: The overview of safety incidents can guide strategies for improving care in the institution under study and collaborate with other health services in identifying risk situations for hospitalized children.